Regulation of P-Glycoprotein during Oxidative Stress - Aleksey V. Shchulkin; Yulia V. Abalenikhina; Olga V. Kosmachevskaya; Alexey F. Topunov; Elena N. Yakusheva (MDPI AG, 2024)
P-glycoprotein (Pgp, ABCB1, MDR1) is an efflux transporter protein that removes molecules from the cells (outflow) into the extracellular space. Pgp plays an important role in pharmacokinetics, ensuring the absorption, distribution, and excretion of drugs and its substrates, as well as in the transport of endogenous molecules (steroid and thyroid hormones). It also contributes to tumor cell resistance to chemotherapy. In this review, we summarize the mechanisms of Pgp regulation during oxidative stress. The currently available data suggest that Pgp has a complex variety of regulatory mechanisms under oxidative stress, involving many transcription factors, the main ones being Nrf2 and Nf-kB. These factors often overlap, and some can be activated under certain conditions, such as the deposition of oxidation products, depending on the severity of oxidative stress. In most cases, the expression of Pgp increases due to increased transcription and translation, but under severe oxidative stress, it can also decrease due to the oxidation of amino acids in its molecule. At the same time, Pgp acts as a protector against oxidative stress, eliminating the causative factors and removing its by-products, as well as participating in signaling pathways.